THE FEMINISMS OF THE LATE 60s IN THE UNITED STATES: RADICALS, DISSIDENTS AND ASSIMILATIONISTS - Arbuet Osuna, Camila (Revista de Historia Social y de las Mentalidades, 2019)
The sudden turn of feminisms towards the end of the 60s, observable in its new programs, strategies of visibility and forms of organization, accounts for a ‘68 different, powerful and fragmentary at the same time. A ‘68 that has, at this point, its most pressing center in the Women’s Lib of the United States where the liberal and radical feminist movements are linked and discuss with currents of black power, gay power and hippism. In this work we propose a possible panning of this complex and bellicose scene between 1966 and 1972, reviewing some of the debates, limits and becomings of these exploded feminisms.
Keywords: Feminisms; Sixty; United States; Debats